Fungal Protein – What Is It and What Is the Health Evidence? A Systematic Review Focusing on Mycoprotein - Derbyshire, Emma J.; Delange, Joanne (Frontiers in Sustainable Food Systems, 2021)
Mycoprotein is a protein-rich fungal-derived sustainable food source that was first discovered in the early 1960's. Since then, a sizeable body of research has investigated the health benefits of mycelium protein. Given this, the present publication aims to systematically review the effects of mycoprotein on human health. A literature search of human studies was conducted using PubMed Central, ClinicalTrials.Gov, Google Scholar and a manual search. Sixteen controlled trials, totaling 432 participants were included – of these 5 studies reported total cholesterol, 5 reported on energy intake, 7 on insulin levels, 8 on glucose levels and 4 studied protein response. Risk of bias showed that 7 studies were good quality although heterogeneity was apparent between studies. Results showed that acute mycoprotein ingestion was associated with reduced total cholesterol levels, particularly amongst those with hyperlipidemia. Evidence was less conclusive for effects on blood glucose and insulin levels. Mycoprotein also appears to be a promising bioavailable source of essential amino acids that could induce muscle protein synthesis. Overall, given growing interest in sustainable proteins and accruing health evidence for mycoprotein, firmer embedment with food-based dietary guidelines is now worthy of consideration.